Conductive elastomeric nanocomposites based on oxidation of aniline with silver nitrate via inverse emulsion polymerization. (30th September 2014) - Brook, Irena; Berner, Alex; Tchoudakov, Roza; Suckeveriene, Ran Y.; Narkis, Moshe
<x xml:space="preserve">Abstract</x> The present investigation describes a facile and rapid approach of conductive nanocomposites production and assesses the opportunity of their use as electro‐mechanical sensors. Hybrid materials containing silver and polyaniline nanoparticles reinforcing a thermoplastic elastomeric matrix were studied. The approach developed includes ultrasonically assisted in situ inverse emulsion polymerization of aniline oxidized by a weak oxidant and silver nitrate, and supported with a strong oxidant, ammonia peroxydisulfate. Aniline was doped with dodecylbenzene sulfonic acid in the presence of dissolved styrene–isoprene–styrene thermoplastic elastomer. While conventional polymerization of aniline with silver nitrate takes 2 weeks, by utilization of inverse emulsion polymerization, the reaction time reduces to 5 days. The assistance of a strong oxidant dramatically shortens the reaction time to 30 min. The technique developed results in uniform distribution of polyaniline/silver (PANI/Ag) conductive nanoparticles in the elastomeric matrix. The morphological studies of the films reveal spherically shaped 45 nm Ag particles. The presence of PANI/Ag in the styrene–isoprene–styrene elastomeric matrix enhances the electrical, thermal, and mechanical properties of the nanocomposites. The approach described provides an opportunity of the development of tunable structures and a remarkably distinctive architecture. A rapid electrical resistance response to an applied strain makes the nanocomposites developed useful as sensitive strain sensors. Copyright © 2014 John Wiley & Sons, Ltd.